Go up to Classic Fallacies index
Go down to first subsection This is Not the Fallacy
Go forward to 1=2: A Proof using Complex Numbers
Switch to graphical version (better pictures & formulas)
Go to University of Toronto Mathematics Network
1=2: A Proof using Beginning Algebra
The Fallacious Proof:
Step 1: Let a=b.
Step 2: Then a^2 = ab,
Step 3: a^2 + a^2 = a^2 + ab,
Step 4: 2 a^2 = a^2 + ab,
Step 5: 2 a^2 - 2 ab = a^2 + ab - 2 ab,
Step 6: and 2 a^2 - 2 ab = a^2 - ab.
Step 7: This can be written as 2 (a^2 - a b) = 1 (a^2 - a b),
Step 8: and cancelling the (a^2 - ab) from both sides
See if you can figure out in which step the fallacy lies.
When you think you've figured it out, click on that step and
the computer will tell you whether you are correct or not, and
will give an additional explanation of why that step is or isn't valid.
See how many tries it takes you to correctly identify the fallacious step!
This page last updated: May 26, 1998
Original Web Site Creator / Mathematical Content Developer:
Current Network Coordinator and Contact Person:
Joel Chan - email@example.com
Navigation Panel: Up | Down to First Subsection | Forward | Graphical Version | U of T Math Network Home